2017
DOI: 10.1017/s0029665117000350
|View full text |Cite|
|
Sign up to set email alerts
|

The challenges of control groups, placebos and blinding in clinical trials of dietary interventions

Abstract: 25High quality placebo-controlled evidence for food, nutrient or dietary advice interventions is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 48 publications
0
75
0
Order By: Relevance
“…It is notoriously challenging to minimize bias in RCTs of dietary interventions, although numerous strategies have been recommended . Blinding to treatment allocation of participants and those delivering the intervention is rarely possible, and the nature of dietary interventions involving complex lifestyle and behaviour changes means participants are likely to have a strong preference, which may, in turn, affect adherence and attrition.…”
Section: Discussionmentioning
confidence: 99%
“…It is notoriously challenging to minimize bias in RCTs of dietary interventions, although numerous strategies have been recommended . Blinding to treatment allocation of participants and those delivering the intervention is rarely possible, and the nature of dietary interventions involving complex lifestyle and behaviour changes means participants are likely to have a strong preference, which may, in turn, affect adherence and attrition.…”
Section: Discussionmentioning
confidence: 99%
“…One challenge is the difficulty of identifying an appropriate control when evaluating foods or food patterns. 64 If control participants do not receive a placebo or a comparative intervention, there is strong potential for expectation bias (expected benefit in the intervention group versus expected lack of benefit in the control group). The Women’s Health Initiative Dietary Modification Trial, for example, compared a low fat intervention group with intensive behaviour modification counselling to increase fruit, vegetable, and grain consumption with a “usual diet” group receiving diet related education materials only.…”
Section: Potential and Limitations Of Randomised Trialsmentioning
confidence: 99%
“…Another study reported satisfaction with symptoms in 72.1% of responders at a mean of 15.7 months follow‐up . However, these studies lacked control groups, had high attrition rates and only reported data in those who completed follow‐up appointments and questionnaires, which are common difficulties in long term follow‐up studies of dietary interventions .…”
Section: Fodmap Personalisation (Long‐term Self‐management)mentioning
confidence: 99%
“…However, a systematic review of the quality of randomised controlled trials of the low FODMAP diet identified limitations in their design, including a high risk of bias for the blinding of participants and outcome measurement, selection of control groups and objective evaluation of data . However, it is also recognised that ensuring participant blinding and identifying appropriate controls can be very challenging in dietary intervention trials .…”
Section: Introductionmentioning
confidence: 99%